Kontrak Sosial dan Pemilihan Umum - Sanit, Arbi (Jurnal Penelitian Politik, 2004)
Social contract is a conception about new p ow e r relationship between elite and people which is formulated in order to fulfilladem and for political renewal which is need a continuity, not stagnation nor deterioration. We need to reconstruct any aspect of social contract theory in order to understand about social contract relevance with general election. The general election as a contract social guaranteed rights and obligation of the voters and the leaders. The contract mechanism between voters and political candidate is related by trust. The object of trust it self in general election is morality. The political contract consistency based on trust is a foundation for building a State as a moral entity, which is made by morally human being.